Why Conservation Agriculture in rainfed drylands in Morocco - Moussadek, Rachid; Devkota Wasti, Mina Kumari; Nangia, Vinay (International Center for Agricultural Research in the Dry Areas, 2022)
Crop yield in the rainfed Mediterranean environment in Morocco, the hot spot for climate change, is highly affected by rainfall variability, temperature extremes, and declining soil quality. Several research findings reported that Conservation agriculture (CA) has potential to minimize climatic risk, reduce soil erosion, and improve water use efficiency and soil health compared to conventionally tilled (CT) field in such climatic condition.